Consumer Buying Behaviour: The Impact of Demographic Factors on Consumer Buying Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Consumer Buying Behavior is an important concept of study in the present time to make a product successful in the market. The study of consumer buying behavior gives an understanding to marketers or companies to fulfill the needs and wants of consumers in best possible way because it helps them to extend the market of their product or service and it enables them to provide the features or quality to their products according to exact choice of consumer. The main purpose of this paper is to have an understanding about that how the demographic factors like age, income level, marital status, gender, and family size, family background affects the buying pattern or buying decision of consumers.